How (not What) Shall We Think about Human Rights and Religious Arguments? Public Reasoning and Beyond - Mathias Thaler (e-cadernos ces)
This paper addresses the question of how (not what) we should think about human rights and religious arguments. Thinking about this relationship is today particularly important, because conflicts over human rights in practice often turn around their theoretical problems. Should religious arguments be used to justify human rights? Or do we want human rights to be free from any partisan endorsement so as to avoid divisive interpretations of universal principles? Underlying these hard questions is the issue of justification in view of a plurality of cultural and religious traditions around the globe. If human rights can be transformed so as to defy the charge of Euro-centrism (of being parochially rooted in only one cultural and religious tradition), they need to creatively draw on, not pit themselves against, this plurality. This paper suggests a framework for such a positive and inclusive engagement with various cultures and religions that goes beyond the mainstream liberal model of “public reason”.